Automated identification of innocent Still's murmur using a convolutional neural network - Shekhar, Raj; Vanama, Ganesh; John, Titus; Issac, James; Arjoune, Youness; Doroshow, Robin W. (Frontiers in Pediatrics, 2022)
Background: Still’s murmur is the most prevalent innocent heart murmur of childhood. Auscultation is the primary clinical tool to identify this murmur as innocent. Whereas pediatric cardiologists routinely perform this task, primary care providers are less successful in distinguishing Still’s murmur from the murmurs of true heart disease. This results in a large number of children with a Still’s murmur being referred to pediatric cardiologists. Objectives: To develop a computer algorithm that can aid primary care providers to identify the innocent Still’s murmur at the point of care, to substantially decrease over-referral. Methods: The study included Still's murmurs, pathological murmurs, other innocent murmurs, and normal (i.e., non-murmur) heart sounds of 1473 pediatric patients recorded using a commercial electronic stethoscope. The recordings with accompanying clinical diagnoses provided by a pediatric cardiologist were used to train and test the convolutional neural network-based algorithm. Results: A comparative analysis showed that the algorithm using only the murmur sounds recorded at the lower left sternal border achieved highest accuracy. The developed algorithm identified Still’s murmur with 90.0% sensitivity and 98.3% specificity for the default decision threshold. The area under the receiver operating characteristic curve was 0.943. Conclusions: Still’s murmur can be identified with high accuracy with the algorithm we developed. Using this approach, the algorithm could help to reduce the rate of unnecessary pediatric cardiologist referrals and use of echocardiography for a common benign finding.